Analysis of Factors Affecting The Incidence of Sexual Violence toward Children at Semarang City Integrated Service Center - Yanti, Erny Yuni; Yuniastuti, Ari; Ratna Rahayu, Sri (Universitas Negeri Semarang, 2020)
Child Sexual violence is a universal crime regardless of the age of the child or gender. In 2017, in Semarang City there were 136 cases of child violence, 41 cases of sexual violence, while in 2018 there were 197 cases of child violence totaling 58 cases constituting sexual violence. The purpose of this research is to analyze, the economic status of parents, parental education, parenting types, peers, to the incidence of child sexual violence in the city of Semarang. The research method using the mixed method begins with the use of quantitative methods supported by qualitative methods, using a cross sectional research design. Quantitative data were collected using questionnaires, documentation and interviews, qualitative data were obtained through observations, field notes, and in-depth interviews with parents of victims and victims' assistants by purposive sampling. The research of sampel were victims of sexual violence aged 8-17 years, 35 respondents. Data analysis in this study used the chi square test and test logistic regression and qualitative descriptive analysis. The results of data analysis found the the economic status had an influence on the incidence of sexual violence against children p value 0.041 <0.05 and Parental education, with a p value of 0.012. whereas in the type of foster parents and peers there was no influence on the incidence of child sexual violence with each p value of 0.652 and p value of 0.682. The logistic regression results showed the most influential variable on the incidence of child sexual violence was parental education with an OR obtained 5.306 p value 0.009. The results of qualitative research concluded that low economic status and low parental education have also influenced the child sexual violence in Semarang city.